Spore for the media - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
With effect from Spore 100, printed issues of the magazine, and electronic summaries, will be sent on a complimentary basis to selected leading media outlets, editors and writers throughout the world. The objective is to widen and deepen the reach...